Analisa Perbandingan Produktivitas Pekerja Pasangan Bata Berdasarkan Elevasi Pekerjaan - MUBARAQ, Abd Halil ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Productivity is the fundamental factors that affect the ability to compete in the construction industry, an increase in the level of productivity is related to the time required to complete the work and will directly influence the magnitude of the costs involved, especially coming from a reduction in costs consumed by the workers. The purpose of this study is to determine how much influence the difference in height of masonry work on the productivity of workers resulting in PT. Varindo Lombok Inti. The method used in this study is descriptive analysis method is the study by collecting primary grade and secondary grade. The results obtained are the average productivity level of workers 3 different elevation is 0,032 m2/minutes = 13.36 m2/day to work with elevation 0-100 cm, 0.04 m2/ minutes = 14.78 m2/day to work with elevation 100-200 cm, 0,032 m2/ minutes = 13.415 m2/day to work with elevation 200-300 cm. Age and work experience factors greatly affect the productivity level of the workers produced.